Analysis of the Influence of Influencers and the Word of Mouth System on Purchasing Decisions XX Cosmetic Products - Safaat Yulianto; Afifah Oktafiyani, Eka (Institut Teknologi Statistika dan Bisnis Muhammadiyah Semarang, 2025)
Background: Products that are currently needed by most women are cosmetics. One of Local cosmetics that are now on the rise and are heading to the global market are products XX. One of XX's marketing strategies is to entrust on Celebrity Endorsers. Objective: This study aims to determine the effect of influencer and word of mouth on the decision to purchase XX's products from the students of the Institute of Technology Statistics and Business of Muhammadiyah Semarang using the Structural Equation Modeling–Partial Least Square (SEM-PLS). Respondents in this study as many as 44 active D3 Statistics ITESA Muhammadiyah Semarang who had purchased XX’s products. Methods: Structural Equation Modeling (SEM) method is a development of path analysis and multiple regression, which are both forms of multivariate analysis model. One of the methods that can be used for analysis between variables and indicators is to use Structural Equation Modeling (SEM). Results: The results of the SEM-PLS analysis show that as many as 58% of purchasing decisions for product XX among D3 Statistics students are influenced by the role of influencers and the word of mouth system. Conclusion: In addition to interactions with celebrity endorsers, word communication of mouth has also been shown to have an effect on the use and purchase of a product.